2009
DOI: 10.1111/j.1463-6395.2008.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the ovaries of the primitive aphids Phylloxera coccinea and Phylloxera glabra (Hemiptera, Aphidinea: Phylloxeridae)

Abstract: Szklarzewicz, T., Jankowska, W., Wieczorek, K. and W e gierek, P. 2009. Structure of the ovaries of the primitive aphids Phylloxera coccinea and Phylloxera glabra (Hemiptera, Aphidinea: Phylloxeridae). -Acta Zoologica (Stockholm) 90 : 123-131Ovaries of phylloxerids consist of short telotrophic ovarioles. Ovaries of wingless morphs contain four ovarioles whereas those of winged morphs contain one or two ovarioles. The individual ovariole of the adult female is differentiated into a terminal filament, trophic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
4
21
0
1
Order By: Relevance
“…aphids (Szklarzewicz & Biliński, 1995;Szklarzewicz, 1997Szklarzewicz, , 1998cSzklarzewicz et al, 2000Szklarzewicz et al, , 2002Szklarzewicz et al, , 2009Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Koteja et al, 2003). Within neococcoids arrested oocytes are only present in some representatives of two families (Eriococcidae and Kermesidae) (Szklarzewicz, 1998b).…”
Section: Morphology Of Ovariesunclassified
See 1 more Smart Citation
“…aphids (Szklarzewicz & Biliński, 1995;Szklarzewicz, 1997Szklarzewicz, , 1998cSzklarzewicz et al, 2000Szklarzewicz et al, , 2002Szklarzewicz et al, , 2009Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Koteja et al, 2003). Within neococcoids arrested oocytes are only present in some representatives of two families (Eriococcidae and Kermesidae) (Szklarzewicz, 1998b).…”
Section: Morphology Of Ovariesunclassified
“…aphids, scale insects, psyllids, whiteflies, cicadomorphans, fulgoromor-phans and heteropterans), have shown that in spite of numerous morphological differences between them they share several synapomorphic characters: (1) in each ovariole only a single cluster of germ cells (oocytes and trophocytes) is present, (2) in each cluster more than one oocyte develops and (3) the centre of the tropharium is occupied by a common cytoplasmic area filled with microtubules, termed a trophic core (e.g. Büning, 1985;Książkiewicz-Kapralska, 1985;Huebner, 1981;Biliński et al, 1990;Simiczyjew et al, 1998;Szklarzewicz, 1998a;Štys et al, 1998;Szklarzewicz et al, 2000Szklarzewicz et al, , 2009. In contrast to the ovarioles of other hemipterans, the ovarioles of scale insects do not possess terminal filaments and contain a small number of germ cells in each ovariole and single oocyte in the vitellarium (scale insect synapomorphies) (Książkiewicz, 1980;Szklarzewicz & Biliński, 1995;Szklarzewicz, 1997Szklarzewicz, , 1998aKoteja et al, 2003;Szklarzewicz et al, 2002Szklarzewicz et al, , 2005Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Niżnik & Szklarzewicz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…yolk granules and lipid droplets) in its cytoplasm. During choriogenesis, as a result of the synthetic activity of follicular cells the oocyte becomes covered with egg envelopes (for a detailed description of ovaries of aphids see Büning, 1985;Szklarzewicz et al, 2000Szklarzewicz et al, , 2009Michalik et al, 2013). In viviparous females the oocyte growth stops at the stage of previtellogenesis.…”
Section: Gross Morphology Of the Ovarymentioning
confidence: 99%
“…Within aphids, only representatives of the family Phylloxeridae (superfamily Phylloxeroidea) do not contain endosymbiotic microorganisms (Buchner, 1965;Szklarzewicz et al, 2009). Aphids belonging to the family Adelgidae (superfamily Adelgoidea) may harbour gamma-or/and betaproteobacterial endosymbionts (Toenshoff et al, 2012a, b;von Dohlen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At this place, a clear remark is that a different strategy leading to the storage of eggshell precursors in a short time was observed in parasite insects such as Hemiptera or Mallophaga (Biliński and Jankowska, ; Michalik et al, ; Pyka‐Fościak and Szklarzewicz, ; Simiczyjew et al, ; Szklarzewicz et al, ; Vogelgesang and Szklarzewicz, ). In contrast to most insects in which the process of choriogenesis begins after the completion of vitelogenesis, these processes run simultaneously in aphids and scale insects (Michalik et al, ; Pyka‐Fościak and Szklarzewicz, ; Szklarzewicz et al, ; Vogelgesang and Szklarzewicz, ). According to Szklarzewicz et al (), this atypical situation allows for the occurrence of several generations of insects per year and the deposition of eggs with completed eggshells before winter.…”
Section: Discussionmentioning
confidence: 99%